Ideologies that justify political violence. (August 2020) - Webber, David; Kruglanski, Arie; Molinario, Erica; Jasko, Katarzyna
Highlights: Ideologies that promote terrorism should avoid content that resonates with constructs related to the perpetuation of the status quo. Ideologies can operate on significance need through tactics that moralize values and portray violence as a remedy to collective grievances. Ideologies whose content resonates with the need for cognitive closure are more likely to promote and justify violence. Religious and right-wing ideologies, because they appeal to significance and epistemic needs, may be more likely to promote extreme violence. Abstract: The present review identifies a variety of tactics that are often employed by ideologies to promote and/or justify political violence. The review builds on a social psychological framework that identifies important existential and epistemic needs that motivate individuals to become ideological extremists and discusses the mechanisms through which ideological narratives that promote political violence can serve these needs. We end the review by discussing two broad variants of ideology (religious and conservative) that should be particularly apt at implementing these tactics.